Gender and the Effect of Working Hours on Firm-Sponsored Training - Matteo Picchio; Jan C. van Ours (Institute for the Study of Labor (IZA), 2015)
Using employees' longitudinal data, we study the effect of working hours on the propensity of firms to sponsor training of their employees. We show that, whereas male part-time workers are less likely to receive training than male full-timers, part-time working women are as likely to receive training as full-time working women. Although we cannot rule out gender-working time specific monopsony power, we speculate that the gender-specific effect of working hours on training has to do with gender-specific stereotyping. In the Netherlands, for women it is common to work part-time. More than half of the prime age female employees work part-time. Therefore, because of social norms, men working part-time could send a different signal to their employer than women working part-time. This might generate a different propensity of firms to sponsor training of male part-timers than female part-timers.
Keywords: C33; C35; J24; M51; M53; 330; part-time employment; working hours; firm-sponsored training; gender; human capital